Westphalia in Carl Schmitt: another Legend (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
Carl Schmitt was one of the Westphalian policy big supporters. The balance, the self-control, the neutrality and the coexistence linked to the Ius publicum europaeum, which was born with the Peace of Westphalia, show themselves, according to Schmitt, as coordinating axis of a pluriverse of nations where there is no religious principles that guide the political action, nor any power that exercise his leadership over the rest. The purpose of this essay is to show that the Westphalian philosophy suffered from the beginning from a hegemonic eagerness, not only at a practical level, but especially inside her definition. The own concept of Westphalia as balance between nations based on the state sovereignty is contradictory, since the sovereignty tends to her highest expansion and power. We discover then, a simulation of peace that shows his real identity in the third colonial space, where the real confrontation between European nations has place.